Violence of the Anti-Islamic Discourse: Analysis of Pope Urban II and His Speech at the Council of Clermont - Polat, Ziya (Journal of Al-Tamaddun, 2024)
The impact of an impassioned speech on an audience is undeniable. Throughout history, influential speeches have played a significant role in major turning points and new beginnings. The Crusades, within the context of the ‘power of speech’, have been a crucial period in history. This article focuses on Pope Urban II, the driving force behind the Crusades, and his speech at the Council of Clermont. His life, path to the papacy, and activities thereafter have been primarily examined to understand the background of the Crusades. The article then explores topics including the oppression of Eastern Christians, the vandalism of religious sites, the seizure of Bayt al-Maqdis, and the mistreatment of pilgrims, all of which were cited in the Pope’s speech as justifications for the Crusades. These were discussed and analysed through the data recorded in the chronicles of the period as the text of the speech. The analysis has focused on the violent elements in the anti-Islamic discourse, which are seen as the main problem. Additionally, the article discusses the Pope’s use of incitement in his speech to rally support for the Crusades. It shows how he persuaded Catholic societies to join the expedition, ultimately leading to the Crusades. The article concludes that the armies of the First Crusade, which set out for the East due to the Pope’s intense efforts, did not hesitate to apply violence against Muslims based on the Pope’s discourse in the places they occupied.